Testing strong line metallicity diagnostics at z ∼ 2. Issue 3 (14th September 2018) - Patrício, V; Christensen, L; Rhodin, H; Cañameras, R; Lara-López, M A
ABSTRACT: High-$z$ galaxy gas-phase metallicities are usually determined through observations of strong optical emission lines with calibrations tied to the local Universe Recent debate has questioned if these calibrations are valid in the high-$z$ Universe. We investigate this by analysing a sample of 16 galaxies at $z$ ∼ 2 available in the literature, and for which the metallicity can be robustly determined using oxygen auroral lines. The sample spans a redshift range of 1.4 < $z$ < 3.6, has metallicities of 7.4–8.4 in 12+log (O/H) and stellar masses ∼10 7.5−11 M⊙ . We test commonly used strong line diagnostics ( R23, O3, O2, O32, N2, O3N2, and Ne3O2 ) as prescribed by four different sets of empirical calibrations, as well as one fully theoretical calibration. We find that none of the strong line diagnostics (or calibration set) tested perform consistently better than the others. Amongst the line ratios tested, R23 and O3 deliver the best results, with accuracies as good as 0.01–0.04 dex and dispersions of ∼0.2 dex in two of the calibrations tested. Generally, line ratios involving nitrogen predict higher values of metallicity, while results with O32 and Ne3O2 show large dispersions. The theoretical calibration yields an accuracy of 0.06 dex, comparable to the best strong line methods. We conclude that, within the metallicity range tested in this work, the locally calibrated diagnostics can still be reliably applied at z  ∼ 2. However, we caution that for ${\sim }60{{\ \rm per\ cent}}$ of our sample the observed R23 line ratios were out of the range of applicability of some of the calibrations tested.